Deltageren som museumsaktivist - Thobo-Carlsen, Mette (K&K - Kultur og Klasse, 2014)
Since the 1960s, a ’theatricalization’ of contemporary art and culture has questioned the modernist ideal of the autonomy of art, highlighting instead the performativity and sociality of art as event. The performative and theatrical viewer-involving tendency in art has redefined the relations between art, context and viewer and inspired many museums to rethink the political rationality implied in their social role as authoritative producers of knowledge and their educative and civilizing functions. The museum - once considered an isolated and privileged public space reserved for a small section of citizens - is today developing new museum policies and strategies based on performative and participatory forms of knowledge production, thus aiming to play a more active and perhaps critical role in constituting new social relations and mobilizing new collectivities and communities. In this context, the present article wishes to suggest a performative reading of the art exhibition The Model: Palle Nielsen from 2014 at ARKEN Museum of Modern Art, in order to understand the various performative modes of participation which the art installation makes possible. The article explores what makes the artwork political, how it achieves and performs political agency and to what effect, thus aiming to redefine the political in art not in terms of content but as unforeseeable effects of the performativity of the aesthetic form.